Left bundle branch stimulation in diffuse electrical heart disease in a pediatric patient - Cueva-Parra, Angel (2022)
Left bundle branch stimulation is a second-line strategy in patients where His bundle stimulation is not optimal. Currently, no cases of left bundle branch stimulation have been reported in patients with diffuse electrical cardiac disease or in the pediatric population.